Design and mechanical optimization of multidirectional pressure-preserved coring system for deep-earth resource exploration - Liu, Guikang; Xie, Yachen; Li, Cong (International journal of mining science and technology, 2025)
Pressure-preserved coring technologies are critical for deep-earth resource exploration but are constrained by the inability to achieve multidirectional coring, restricting exploration range while escalating costs and environmental impacts. We developed a multidirectional pressure-preserved coring system based on magnetic control for deep-earth environments up to 5000 m. The system integrates a magnetically controlled method and key pressure-preserved components to ensure precise self-triggering and self-sealing. It is supported by geometric control equations for optimizing structural stability. Their structure was verified and optimized through theoretical and numerical calculations to meet design objectives. To clarify the self-triggering mechanism in complex environments, a dynamic interference model was established, verifying stability during multidirectional coring. The prototype was fabricated, and functional tests confirmed that it met its design objectives. In a 300-meter-deep test inclined well, 10 coring operations were completed with a 100% pressure-preserved success rate, confirming the accuracy of the dynamic interference model analysis. Field trials in a 1970-meter-deep inclined petroleum well, representative of complex environments, demonstrated an in-situ pressure preservation efficiency of 92.18% at 22 MPa. This system innovatively expands the application scope of pressure-preserved coring, providing technical support for efficient and sustainable deep resources exploration and mining.